Data source mapping: an essential step for health inequality monitoring. (3rd December 2018) - Hosseinpoor, Ahmad Reza; Nambiar, Devaki; Suparmi,; Kusumawardani, Nunik
ABSTRACT: The task of health inequality monitoring is not possible without the availability of appropriate and high-quality data at various levels. Data source mapping – a process by which data sources are systematically enlisted, their properties detailed and each source appraised for the purposes of monitoring – is an essential initial step for health inequality monitoring. We outline a simple process along with a template for data source mapping and its application in Indonesia, concluding with the lessons learned from this process, in terms of both challenges as well as the opportunities and advantages arising from the use of equity-related data from the Indonesian health information system.